Determinants of Local Government Financial Performance Efficiency - Endiyatmo, Daya Tistaresdo; Ananda, Candra Fajri (Journal of Development Economic and Social Studies, 2026)
Improving the efficiency of local government financial performance is essential for enhancing public service delivery and ensuring sustainable regional development. However, many local governments continue to face challenges related to limited fiscal capacity, dependence on intergovernmental transfers, and inefficiencies in financial management. This study aims to examine the determinants of the efficiency of local government financial performance by analyzing the effects of Local Own-Source Revenue (PAD), capital expenditure, intergovernmental transfers, budget surplus (SILPA), and audit opinions issued by the Audit Board of Indonesia (BPK). A quantitative approach was employed using panel data regression on 38 cities and regencies' governments over the period 2013-2024, resulting in 456 observations. Financial performance efficiency was measured using the ratio of regional expenditure to regional revenue. The findings reveal that PAD, capital expenditure, intergovernmental transfers, and BPK audit opinions have a positive and significant effect on financial performance efficiency, whereas SILPA has a negative and significant effect. These results imply that strengthening local fiscal capacity, optimizing expenditure allocation, and improving financial accountability can enhance the efficiency of local government financial management and support better governance outcomes.